PROPHYLAXIS OF VENOUS THROMBOEMBOLIC COMPLICATIONS IN PATIENTS WITH ACTIVE ONCOLOGICAL DISEASE, RECEIVING MEDICAL ANTI-CANCER CHEMOTHERAPY IN OUTPATIENT CONDITIONS. ROLE OF APIXABAN - Yu. A. Fedotkina; E. P. Panchenko («REMEDIUM GROUP» Ltd., 2020)
Oncological disease is one of the most important risk factors for venous thromboembolic complications (VTEC). The treatment of an already confirmed VTEC in an oncological patient is always associated with additional difficulties, which are related to drug interactions, which may affect the efficacy of chemotherapy or the efficacy and safety of anticoagulant therapy. VTEC prophylaxis for oncological patients could take the lead. However, it remains unclear whether medication-based thromboprophylaxis should be given to patients with oncological diseases, as thrombotic risks and risks of hemorrhagic complications vary widely and depend on the type of cancer, the stage of the process and the anticancer treatment provided. The criteria for thromboprophylaxis are clearly defined for hospitalized patients and patients undergoing surgical treatment. However, long-term cancer therapy is mainly carried out in outpatient conditions. Chemotherapy increases the risk of developing VTEC. The new targeted therapy, which is performed independently or in combination with traditional chemotherapy, does not reduce the risk of developing VTEC. Low-molecularheparins are the «gold standard» for the treatment and prevention of VTEC in cancer patients.When using LMWH, especially in groups of oncological patients with high thrombotic risk, a reliable decrease in thrombotic events was shown, but bleeding remains the main adverse effect, leveling out the benefit of medical thromboprophylaxis. Another attempt to increase the safety of thromboprophylaxis is the use of direct oral anticoagulants (DOACs). The article deals with modern provisions of medical thromboprophylaxis in patients with cancer, as well as the possibility of using DOACs, in particular apixaban, for the prevention of cancer-associated VTEC.